The influence of rigid and intermediate soil on the structural response of an isolated building with a lead core for educational use - Moreno, Javier (2024)
One of the problems in Peru is that it is in the ring of fire and therefore vulnerable to seismic events. In addition, it has different types of soils such as very rigid (S1), intermediate (S2), flexible (S3) and some with special conditions (S4), as well as different types of seismic zones such as Zone 1, 2, 3, and 4. That is why the seismic response of an isolated regular structure was investigated by comparing and evaluating two different types of soil, which were very rigid and intermediate. For this, a three-story fixed base structure model was used. Later, these models were reconstructed to consider this structure in isolation and not as a fixed base structure as it originally was. Finally, the analysis showed the displacements, the drifts, the forces at the base, and the periods. In conclusion, the results of the analysis determined that the type 1 soils are safer against than type 2 soils in a seismic response. After the results were obtained from these parameters, the ETABS program revealed that type 1 soil has lower parameters than type 2 soil. Verifying that the stratigraphy in predominance of rocks helps to reduce seismic waves.